Pendampingan Lean Canvas Business sebagai Strategi Pertumbuhan Berkelanjutan UMKM Kuliner Kota Batam - Ulfah, Mutia; Oktarici, Eddo Nanda; Devano, â Alrido Martha; Putri, Ancala Laras; Rahman, Fuad Arif; Lawita, â Nadia Fathurrahmi; Sinaga, Inggrid Wahyuni; Sabrina, â Nova; Lestari, Anggun Dwi; Syafriandana, Dava; Ananda, Lyra; Ranendra, â Muhammad Egha Octa; Yuliana, Natasha; Wahyuni, Ninda (Politeknik Negeri Batam, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are vital in the Indonesian economy, especially in Batam City. The culinary sector, as one of the drivers of the creative economy, needs help in terms of business management and business legality. Bizhub Polibatam as a Center of Excellence in Business & Community Service under Polibatam to strengthen the entrepreneurial ecosystem and support the growth of MSME business foundations, especially in Batam Island. This community service activity aims to assist culinary MSME players in Batam City in designing business models using the Lean Canvas method and facilitating making Business Identification Numbers (NIB). This program involves 20 culinary MSMEs in Batam City. The activity results showed an increased understanding of MSME players about business models and the importance of business legality, with 100% of participants successfully assisting in making NIB and creating a Lean Canvas model in their business.